Damage Analysis of Subsea Pipeline Due To Anchor Drag with Finite Element Method - Windadi, Agung
The pipeline from offshore to the mainland is not only in locations with little human activity but it is also not uncommon to pass through a public port where there is a lot of vessel activity above the pipeline. Dense shipping activities at the port cause many ships to lower their anchors to the sea, this causes potential damage to the pipeline due to being hit by anchors that fall or get stuck and eventually dragged by anchors pulled by the ship. Pipes that are dragged by the anchor need to be analyzed to find out how much maximum displacement can be drawn by the anchor, local deformation, the amount of stress and strain that occurs. In this study modeling was done with the finite element method using ABAQUS software to analyze the occurrence of pipes that were dragged by anchors in the case of a pipe accident owned by PT. Pertamina RU V Balikpapan with two types of seabed, sand seabed and clay seabed. The analysis carried out is by conducting global pipe modeling and local pipe modeling. Global pipeline model is to determine the maximum displacement of the pipe dragged by the anchor, while the local pipe modeling is to find out the stress distribution, strain, and also the form of deformation in the pipe. The results of global analysis on the clay seabed produce a maximum displacement of 705.5 m while on the seabed the sand produces a maximum displacement of 238.7 m, both of this results are obtained from condition where the same criteria are applied. The results of local analysis on the clay seabed produce a maximum stress of 455.1 MPa with a maximum strain of 25% whereas in the local model with the sand floor the maximum stress is 455.1 MPa with a maximum strain of 15.5%. The results of this modeling also show that the influence of the seabed type is one of the significant factors in the differences in the results obtained.